The Customary Marriage of Samin Penghayat in Tulang Bawang Regency, Lampung, Indonesia - Muslimin, Ahmad; Asnawi, Habib Shulton; Dahlan, Rahmat; el-Hajjami, Aicha; Alamsyah, Alamsyah; Mahmudah, Siti (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
The marriage of the Samin people in Lampung Province is conducted in a customary manner. The Samin people experience many obstacles in the process of registering their marriage officially through state institutions. The purpose of this article is to describe the Samin traditional marriage and then analyze the reasons why the Samin community conducts traditional marriages. This article uses a qualitative method, the object of research was conducted on the Samin community in Tulang Bawang Regency Lampung. Primary data sources were obtained directly from Samin traditional leaders and the community who performed traditional marriages. Secondary data sources were obtained through Samin guidebooks and journals related to Samin studies. Data collection techniques used are observation, interviews and documentation. The results showed that the marriage process of the Samin community in Tulang Bawang Regency was carried out through several stages including: (1) nyumuk, (2) ngendek, (3) nyuwito, (4) paseksen, (tingkep). Samin traditional marriage does not yet have authentic legality. The legal status of the marriage is only valid in the eyes of the customary law of the adherents but not in the eyes of Indonesian marriage law. The reasons why Samin people do not officially register their marriages are 1). The Samin organization has not been registered with the Directorate of Trust of the Ministry of Culture as a marriage registration officer 2). Samin leaders have not been registered with the Ministry because they do not have a Registered Certificate (SKT). 3) Their ancestors did not teach that marriage should be registered.